STATUS MIKRONUTRIEN REMAJA PUTRI DENGAN RIWAYAT BERAT BADAN LAHIR RENDAH (BBLR) - Octavia, Lestaria; Karyadi, Elvina; Alisjabana, Bachti; Widjaja, Maria (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThe objective of this study was to assess the micronutrient and nutritional status among female adolescents having low birth weight history and normal birth weight history. Research design for this particular research was nested cohort in community level. Subjects was chosen by simple randomization, based on data collected by Frontiers for Health Foundation and Padjajaran University, Bandung. The measurement of micronutrients status (Hb, retinol plasma, and urinary iodine excretion), anthropometric, history of disease, semi quantitative food frequency questionnaire was collected to make comparison between female young adolescent with low birth weight and normal birth weight history. The prevalence of iron deficiency anemia (IDA), vitamin A deficiency (VAD), and iodine deficiency among all subjects were 9.9%, 12.9%, and 40.7%, respectively. The mean concentration of blood hemoglobin, plasma retinol and iodine excretion were not significantly different between low birth weight (LBW) and normal birth weight (NBW) group. Nutritional status, disease during the last three months, current nutritional status, food intake and onset of menstruation were not significantly different between group. In conclusion, micronutrient status, nutritional status, food intake and morbidity status in female adolescents with LBW and NBW history were not different.Keywords: iodine, iron, low birth weight, normal birth weight, vitamin AABSTRAKTujuan penelitian ini adalah mengukur status mikronutrien dan gizi remaja putri yang memiliki riwayat berat badan lahir rendah dan berat badan normal. Desain penelitian ini adalah nested cohort retrospective untuk tingkat komunitas. Subjek penelitian dipilih berdasarkan randomisasi sederhana, berdasarkan data cohort yang dikumpulkan oleh Yayasan Frontriers for Health dan Universitas Padjajaran, Bandung. Pengukuran status mikronutrien (Hb, plasma retinol, dan kadar iodium dari ekskresi urin), pengukuran antropometri, riwayat penyakit yang diderita dan pengumpulan data mengenai asupan makanan dilakukan perbandingan antara remaja putri yang memiliki berat badan normal dan berat badan lahir rendah. Prevalensi anemia kekurangan zat besi, kekurangan vitamin A dan kadar iodium dari ekskresi urin pada semua subjek adalah 9,9%, 12,9%, dan 40,7%, secara berurutan. Konsentrasi rata-rata dari hemoglobin darah, plasma retinol dan kadar iodium dari ekskresi urin tidak berbeda secara nyata antara remaja putri dengan berat badan lahir rendah dan berat badan normal. Status gizi, penyakit yang diderita selama tiga bulan terakhir, asupan makanan, dan usia mulai mengalami menstruasi tidak berbeda secara nyata antara remaja putri dengan berat badan normal dan berat badan rendah. Status mikronutrien, status gizi, asupan makanan, dan status morbiditas pada remaja putri dengan berat badan lahir rendah dan berat badan normal tidak terdapat perbedaan yang nyata.Kata kunci: BBLN, BBLR, iodium, vitamin A, zat besi